Resource Translocation Modelling Highlights Density-Dependence Effects in Fruit Production at Various Levels of Organisation - Génard, Michel; Lescourret, Françoise; Bertin, Nadia; Vercambre, Gilles (Frontiers in Plant Science, 2022)
The size of fruit cells, seeds and fruits depends on their number. Could this density dependence effect result from sugar resource sharing and, if so, does it involve phloem sugar flow or the intensity of sugar unloading to the sink? A density-dependence model (DDM) describing these processes was designed and parameterised for six species at five levels of organisation: cells and seeds within fruits, fruits within clusters, fruits within plants, and plants within plots. Sugar flow was driven by phloem conductance, determined by parameters apha, governing the shape of its relationship to population size, and tau, its value for a population size of one. Sugar unloading followed Michaelis-Menten kinetics with parameters Vm (maximal unloading rate) and Km (Michaelis constant). The DDM effectively reproduced the observed individual mass dynamics, the undercompensating density dependence observed in most species at all sub-plant levels and the undercompensating, exact and overcompensating density dependence observed at plant level. Conductance (tau) was a scaling factor varying with level of organisation. Vm was positively correlated with density dependence, and alpha was negatively correlated with density dependence only if the plant-within-plot level was not considered. Analysis of the model's behaviour indicates that density dependence of fruit growth could be a result of sugar sharing, and that both phloem sugar flow and sugar unloading contribute to these effects.